Application of the full nitrogen dose at decreasing rates by foliar spraying versus conventional soil fertilization in common wheat - Manuel Ferrari; Vittorio Bertin; Pranay Kumar Bolla; Francesco Valente; Anna Panozzo; Gianluigi Giannelli; Giovanna Visioli; Teofilo Vamerali (Journal of Agriculture and Food Research)
Foliar fertilization is increasingly recognized as a sustainable agronomic practice, yet its full potential to enhance nitrogen use efficiency (NUE), reduce application rates, and improve wheat grain quality remains largely underexplored. This study evaluated a two-year field trial comparing nitrogen fertilization applied solely through repeated foliar spraying at reduced doses (96, 80, and 64 kg N ha−1) using urea-ammonium-nitrate (UAN) compared to conventional soil fertilization at a standard rate of 160 kg N ha−1. Here it was demonstrated that foliar application at 96 kg N ha−1 achieved grain yields comparable to conventional fertilization (6.80 vs. 7.05 t ha−1) while slightly improving root and shoot growth. Reduced doses also significantly enhanced the glutenins-to-gliadins ratio, total glutenins content (+14 %), and nitrogen use efficiency (NUE: 118.1 vs. 47.5 kg grain DM kg−1 N supplied) but with a 14 % yield reduction at the lowest fertilizer dose (64 kg N ha−1).These findings demonstrate that foliar fertilization can maintain wheat productivity while reducing nitrogen input by up to 40 %, enhancing NUE and grain quality. This strategy also provides fertilizer savings and environmental benefits, with potential applications in drought-prone areas. Future research should focus on optimizing application rates and assessing long-term economic and environmental impacts.